The Impact of Automotive After-Sales Service Quality and Alternative Attractiveness on Customer Loyalty - Zainil Hanim Saidin; Sany Sanuri Mohd. Mokhtar; Rohaizah Saad; Rushami Zien Yusoff (International Journal of Supply Chain Management, 2018)
This study intends to explore the impact of an industry-specific dimension of service quality in automotive after-sales service and how it influences the level of customer loyalty towards Malaysian national carmakers. Each service industry carries different characteristics of consumer behavior and thus, an industry-specific measure of service quality to capture the uniqueness of different service setting is required. In relation to that, this study has evaluated service quality in automotive after-sales service as a second-order construct which allows for identification of the relative importance of each dimension in influencing the level of customer loyalty. Aside from that, the fierce competition from the non-national brands in Malaysian automotive market and the attractive offers made by the alternative workshops for car service maintenance and repair have motivated this study to empirically examines the competition factor of alternative attractiveness and its influences on customer loyalty. The data collected through the technique of intercept survey in systematic sampling from 312 respondents were analyzed using PLS-SEM. The findings revealed that customer service was the most important dimension of service quality that contributes to the positive relationship with customer loyalty. Meanwhile, support service was found as the impotent element of service quality dimension, however, the positive significant relationship of service quality with customer loyalty showed that support service is still important to capture a higher level of customer loyalty. Aside from that, the finding also showed that the competition variable of alternative attractiveness was not a significant contributor to influence the level of customer loyalty. Further, this study benefited the Malaysian national carmakers as it provides empirical evidence on the relative importance of service quality dimension. The role of competitors also revealed to help in strategic decision-making in which may allow the national carmakers to sustain as a market leader in the local automotive arena.